Effect of water spray on friction and wear behaviour of noncommercial and commercial brake pad materials - ELTAYEB, N; LIEW, K (ELSEVIER SCIENCE SA, 2008)
The reduction in the friction coefficient to unacceptable levels for frictional brake pad applications in a rainy and humidly environment is considered as a serious problem as it influences the safety of the vehicle. Thus, in the present work, particular emphasize were given to the effect of water spray on the level and behaviour of friction and wear characteristics of frictional brake pad (FBP) materials. Four different non-commercial FBP materials (NF1, NF2, NF4, and NF5) were developed and evaluated along with other two chosen commercial FBP materials (CMA and CMB) using a small-scale tribo-tester of pad-on-disc type. The results confirmed that in spite of spraying water to the disc, no evidence of HD water film could be observed. Hence the friction behaviour was influenced by factors other than HD film. The values of friction coefficient obtained under wet condition were in the range of dry friction, mixed and boundary lubrication friction. For instant, some values of friction coefficient for NF1 &NF4 were less than 0.05 which was in the range of friction in mixed lubrication. Regardless of the type of brake pad materials, the results indicated that spraying water eliminates the establishment of the transfer layer at the friction interface and suppresses the temperature rise in the disc and so the formation of the char or other reaction products such as oxides. Besides, wear rate of all FBP materials behaved linearly with contact pressure. Qualitative assessment of the SEM morphologies of brake pad surfaces confirmed that tribofilms were hardly formed in wet braking. in addition, all brake pad surfaces showed formation of contact plateaus "patches" and disintegrations of various sizes and locations depending on the braking condition. Furthermore, the removal of material was associated with either mechanical crushing action performed by entrapped wear debris or due to disintegration of plateaus which were accelerated by spraying the water. (C) 2008 Elsevier B.V. All rights reserved.